Methods : An Application in Portugal (Forest Science, 2013)
The practice of multicriteria forest management planning is often complicated by the need to explicit a priori goals and preferences of the decisionmaker. This manuscript aims at describing an approach that may take advantage of a posteriori preference modeling to facilitate the specification of the levels of achievement of various objectives in a typical forest management planning framework. The goal is to provide information about nondominated points in the feasible set in the criteria space (FSCS) so that decisionmakers may take advantage of trade-off information. The emphasis is on demonstrating the potential of adaptive search methods to enhance decisions when three or more criteria are considered. The approach combines the use of mathematical programming and interactive decision maps techniques. It is shown how the estimation refinement method may be used to approximate the Pareto frontier of a typical model I linear programming model. It is further shown how the feasible goals method/interactive decision maps method may be used to retrieve a solution selected by stakeholders from interactive decision maps depicting the Pareto frontier. Results are discussed for a large-scale test application encompassing over 1 million ha of cork and holm oak forest ecosystems in southern Portugal. FOR.SCI.

Designing decision support tools for Mediterranean forest ecosystems management: a case study in Portugal (Ann. For. Sci., 2005)
The effectiveness of Mediterranean forest ecosystem management calls for the conceptualization and implementation of adequate decision support tools. The proposed decision support system encompasses a management information system, a prescription simulator, a constraint generator and a set of management models designed to solve decision problems. Emphasis is on the architecture of the prescription simulator and its linkage to the three other modules, as well as on methods for reporting and visualizing solutions. Results are discussed for a real world test case – Serra de Grândola, a management area with about 18 600 ha comprising 860 cork oak (Quercus suber L.) land units. Cork oak silviculture adds complexity to the traditional forest management problem. Results show that the devised system is able to address effectively the integration of ecosystem data, silviculture, growth-and-yield and management models. They further suggest that the proposed system architecture may help address the complexity of Mediterranean ecosystem management problems.